2015
DOI: 10.1007/s00299-015-1777-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence that rough endoplasmic reticulum is the site of calreticulin translation in Petunia pollen tubes growing in vitro

Abstract: Key messageIn germinating pollen grains and growing pollen tubes, CRT is translated on ER membrane-bound ribosomes in the regions where its activity is required for stabilization of tip-focused Ca2+gradient.AbstractPollen tube growth requires coordination of signaling, exocytosis, and actin cytoskeletal organization. Many of these processes are thought to be controlled by finely tuned regulation of cytoplasmic Ca2+ in discrete regions of the tube cytoplasm. Most notably, a mechanism must function to maintain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…One important aspect of this optimized cellular growth is the presence of local pH gradients with an acidic apex region and an alkaline band in the clear zone followed by a subapical region of acidic pH (15,16). This complex organization of events demands an optimized protein synthesis machinery (17), as critical protein components like calreticulin have been shown to be continuously synthesized during pollen tube growth (18).…”
Section: Introductionmentioning
confidence: 99%
“…One important aspect of this optimized cellular growth is the presence of local pH gradients with an acidic apex region and an alkaline band in the clear zone followed by a subapical region of acidic pH (15,16). This complex organization of events demands an optimized protein synthesis machinery (17), as critical protein components like calreticulin have been shown to be continuously synthesized during pollen tube growth (18).…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise mechanism is still unclear, stabilization of a tip-focused Ca 2+ gradient is critical for pollen germination and pollen tube growth (see reviews by Hepler et al 2012 ; Steinhorst and Kudla 2013 ). We previously showed that in Petunia pollen tubes growing in vitro, CRT is translated on ER membrane-bound ribosomes and accumulated in the ER at the subapical zone of the tube, where plays a role in stabilizing Ca 2+ homeostasis that is required for actomyosin-dependent cytoplasmic streaming, organelle positioning, vesicle trafficking, and cell wall biogenesis (Suwińska et al 2015 , 2017 ). Thus, we concluded that internal Ca 2+ stores involving CRT activity are crucial for proper pollen tube elongation.…”
Section: Discussionmentioning
confidence: 99%
“…For detailed ultrastructural analysis, elongated WT and si1 PhCRT pollen tubes (cultivated for about 4–5 h) were fixed and prepared for transmission electron microscopy as previously described (Suwińska et al 2015 ). In brief, pollen tubes were fixed with 2% glutaraldehyde (Sigma-Aldrich) in 0.1 M PBS, pH 7.2, for 2 h at room temperature followed by overnight at 4 °C, and then post-fixed with 2% osmium tetroxide (Sigma-Aldrich) in PBS for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Immunolocalization and FISH of CRT and its transcripts in pollen tubes were performed exactly according to the protocols described previously (Suwińska et al 2015 ). In brief, for FISH, elongated WT, si1 PhCRT , and scr_si1 PhCRT pollen tubes (cultivated for about 4–5 h) were fixed in freshly prepared 4% formaldehyde (Polysciences) in PBS, pH 7.2, enzymatically digested, and permeabilized with 0.1% saponin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation